Village Law, Village Government, And Community Empowerment: The Case Study in Sub-district of Kedawung, Cirebon - Ros Awaliyah Rosadah; Muhammad Iqbal Bin Samadi (Universitas Muhammadiyah Tangerang, 2022)
ABSTRACTThis study aims to analyze the effect of policy implementation of Law Number 6 of 2014 on rural community empowerment in the Kedawung Sub-district, Cirebon Regency. In this study, policy implementation was described in the bureaucratic structure. This descriptive research applied a quantitative approach. The samples used were 100 respondents, and the research method employed was the descriptive analysis method. Data were collected through the distribution of questionnaires as the main instrument. Based on the study results, the influence of communication describing the implementation of the bureaucratic structure explained the policy implementation by 49.13%. The value of the policy implementation variable could be explained largely by the bureaucratic structure. Then, simultaneously, the effect of the policy implementation of Law Number 6 of 2014 on rural community empowerment was 77.87%. Meanwhile, the remaining 22.13% that participated in determining the achievement of community empowerment were affected by other variables outside of this study. This study concludes that The implementation of Law Number 6 of 2014 concerning Villages had a significant positive effect on the empowerment of rural communities. The strongest indicator of effect was the indicator that the village government’s policies could increase people’s income. The urgency of research on community empowerment is to increase community participation and independent activities through village funds towards superior HR competitiveness and to support regional autonomy through village government which the Village Law constructs. Keywords: Village government, policy implementation, community empowerment ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh implementasi kebijakan undang-undang nomor 6 tahun 2014 terhadap pemberdayaan masyarakat Desa di Kecamatan Kedawung Kabupaten Cirebon. Implementasi kebijakan dijelaskan dalam struktur birokrasi. Penelitian ini bersifat deskriptif dengan pendekatan kuantitatif. Sample yang digunakan sebanyak 100 responden, kemudian metode penelitian yang digunakan adalah metode deskriptif analisis. Pengumpulan data dilakukan melalui penyebaran angket sebagai instrumen utama. Berdasarkan hasil penelitian diketahui bahwa pengaruh komunikasi yang menjelaskan implementasi struktur birokrasi menerangkan implementasi kebijakan sebesar 49,13%. Nilai variable implementasi kebijakan dapat dijelaskan paling besar oleh struktur birokrasi. Kemudian secara simultan pengaruh implementasi kebijakan Undang-Undang Nomor 6 Tahun 2014 terhadap pemberdayaan masyarakat desa sebesar 77,87%. Sedangkan sisanya yang ikut menentukan pencapaian pemberayaan masyarakat sebesar 22,13% ditentukan oleh variabel lain di luar penelitian ini. Penelitian ini menyimpulkan bahwa Implementasi Undang-Undang Nomor 6 Tahun 2014 tentang Desa berpengaruh positif signifikan terhadap pemberdayaan masyarakat desa. Indikator pengaruh yang paling kuat adalah indikator bahwa kebijakan pemerintah desa dapat meningkatkan pendapatan masyarakat. Urgensi dari penelitian tentang pemberdayaan masyarakat yaitu untuk meningkatkan partisipasi dan aktifitas mandiri masyarakat melalui dana desa menuju daya saing SDM yang unggul, dan mendukungn otonomi daerah melalui pemerintah desa yang dikontruksi UU Desa. Kata Kunci : Pemerintah desa, implementasi kebijakan, pemberdayaan masyarakat